POTENSI BANJIR LIMPASAN PERMUKAAN DI SUB DAS MERANGIN TEMBESI DAS BATANGHARI AKIBAT ALIH FUNGSI LAHAN - selfia zalna; ahyuni ahyuni (JURNAL BUANA, 2021)
Abstract This study aims to: 1) determine the area of ​​land use change that occurred in the Merangin Tembesi watershed in the Batanghari watershed in 2009 and 2018. 2) determine the potential for surface runoff flooding before and after the land use change in the Merangin Tembesi sub-watershed in the Batanghari watershed in 2009 and 2018. This type of research is quantitative with a spatial descriptive approach. The method for calculating the area of ​​land use change is through calculate geometry. And in analyzing the potential for surface runoff flooding is done by using the Cook method. Based on the results of the study, it is known that 1) the area of ​​land use change that occurred in the Merangin Tembesi sub-watershed Batanghari watershed changed from 2009 to 2018, where the changes that occurred were greater to the land that was built as land use increased, namely plantations increased by 191738 ha, settlement increased by an area of ​​6758 ha, while the use of forest land decreased by 198932 ha. 2) The potential for surface runoff flooding in the Merangin Tembesi sub-watershed Batanghari watershed in 2009 and 2018 is divided into 4 classes, namely low, medium, high and very high where, in 2009 before the land use change the largest area was found in the high class namely covering an area of ​​5276,919 km², whereas in 2018 after land conversion, the potential for runoff flooding in the Merangin Tembesi sub-watershed region has increased in very high classes to 11463,40172 km².